Psalms 73-150 - Estes, Daniel J. (The New American Commentary Ser., 2019)
The New American Commentary is for those who have been seeking a commentary that honors the Scriptures, represents the finest in contemporary evangelical scholarship and lends itself to the practical work of preaching and teaching..